The crystal structure of 1,2-bis(4-pyridyl)ethane - 4,4-dihydroxydiphenylmethane (1/1), C25H21N2O2 - Cheng Jie; Chen Jue (Zeitschrift für Kristallographie - New Crystal Structures)
C25H21N2O2, monoclinic, C2/c (no. 15), a = 11.041(2) Å, b = 7.859(2) Å, c = 24.131(5) Å, β = 95.26(3)°, V = 2085.1(7) Å3, Z = 4, R gt(F) = 0.0486, wR ref(F 2) = 0.1402, T = 295 K.